Underpinning the Neurobiological Intricacies Associated with Opioid Tolerance - Uniyal A.; Gadepalli A.; Akhilesh; Tiwari V. (My University, 2025)
The opioid crisis is a major threat of the 21st century, with a remarkable juxtaposition of use and abuse. Opioids are the most potent and efficacious class of analgesics, but despite their proven therapeutic efficacy, they have recently been degraded to third-line therapy for the management of chronic pain in clinics. The reason behind this is the development of potential side effects and tolerance after repeated dosing. Opioid tolerance is the major limiting factor leading to the withdrawal of treatment, severe side effects due to dose escalation, and sometimes even death of the patients. Every day more than 90 people die due to opioids overdose in America, and a similar trend has been seen across the globe. Over the past two decades, researchers have been trying to dissect the neurobiological mechanism of opioid tolerance. Research on opioid tolerance shifted toward central nervous system-based adaptations because tolerance is much more than just a cellular phenomenon. Thus, neurobiological adaptations associated with opioid tolerance are important to understand in order to find newer pain therapeutics. These adaptations are associated with alterations in ascending and descending pain pathways, reward circuitry modulations, receptor desensitization and down-regulation, receptor internalization, heterodimerization, and altered epigenetic regulation. The present Review is focused on novel circuitries associated with opioid tolerance in different areas of the brain, such as periaqueductal gray, rostral ventromedial medulla, dorsal raphe nucleus, ventral tegmental area, and nucleus accumbens. Understanding the neurobiological modulations associated with chronic opioid exposure and tolerance will pave the way for the development of novel pharmacological tools for safer and better management of chronic pain in patients. © 2020 American Chemical Society.